PENGARUH PERSEPSI KONSUMEN ATAS GENERAL INTERIOR DAN STORE EXTERIOR TERHADAP NIAT BELI ULANG DI CAFE MUTUALAN - Verdio Setyo Herwanto, Stefanus; Anggita, Meidila; Wardhono, Wisnu (Parahyangan Management Science and Practices Student Review, 2024)
The purpose of this research is to understand consumer perceptions of general interior (X1), store exterior (X2), and repurchase intention (Y) at Cafe Mutualan. The research method employed is explanatory research aimed at explaining whether there is a relationship and influence among the variables studied. The author uses a quantitative approach with a sample of 102 respondents who are familiar with and have visited Cafe Mutualan. The next step is to determine the extent to which general interior and store exterior explain repurchase intention by performing multiple linear regression analysis. The author utilized IBM SPSS 27 software and found that general interior (X1) and store exterior (X2) can explain changes in repurchase intention (Y) at Cafe Mutualan. The coefficient of determination shows that general interior (X1) and store exterior (X2) contribute 8.8% to explaining repurchase intention. Additionally, the multiple linear regression equation reveals that the ability of general interior to significantly explain changes is 0.3098, while store exterior, though not significant, has an effect of 0.0233 on repurchase intention at Cafe Mutualan